PENERAPAN METODE CREDITRISK+ DALAM PENGUKURAN RISIKO KREDIT KENDARAAN BERMOTOR (KASUS PADA PT X) - Meilani, Any (LPPM Universitas Terbuka, 2010)
Identify and measure credit risk by using a method in accordance with the characteristics of finance companies is one of a prudent first step in minimizing potential losses. Potential losses can be seen from the Non Performing Loan (NPL) and recovery rate of the company. Credit risk measurement remains important as preventive and anticipatory measures for a finance company in managing the potential consumer default in fulfilling their obligations. By using 36 months of credit risk in motor vehicles (2006-2008) which includes the number of units of motor vehicles, the amount of exposure, collectability and recovery rate can be calculated expected Loss, unexpected loss and economic capital. Results showed that both the expected Loss and unexpected loss from year to year increase. Also with the economic capital increases annually. However, if the economic value associated with authorized capital owned by PT